2013
DOI: 10.3182/20130619-3-ru-3018.00600
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a framework to support strategic decisions to improve Enterprise Resilience

Abstract: Enterprise resilience is a complex concept that involves different properties and research areas. Based on the literature review, three main properties related to enterprise resilience have been identified: vulnerability, adaptative capacity and recovery ability. On the other hand, an analysis of the current literature approaches to measure and assess enterprise resilience has been described. However, approaches that assess and measure simultaneously the three main properties of enterprise resilience have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
0
15
0
3
Order By: Relevance
“…Despite there is a broad literature about organizational resilience indicators (Horne III and Orr, 1998;Bhamidipaty et al, 2007;Somers, 2009;Sanchis and Poler, 2013;Lee et al, 2013;Seville 2009;Whitman et al, 2013), we have chosen the indicators proposed by Lee et al (2013) because they provide a complete benchmark tool to do the evaluation process. They evaluate the organizational resilience potential based on a questionnaire with 53 items.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…Despite there is a broad literature about organizational resilience indicators (Horne III and Orr, 1998;Bhamidipaty et al, 2007;Somers, 2009;Sanchis and Poler, 2013;Lee et al, 2013;Seville 2009;Whitman et al, 2013), we have chosen the indicators proposed by Lee et al (2013) because they provide a complete benchmark tool to do the evaluation process. They evaluate the organizational resilience potential based on a questionnaire with 53 items.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…However, the items to be evaluated in each category were not discussed. Sanchis & Poler (2013) proposed to measure resilience based on the vulnerability of the organization, its adaptive capacity and recovery ability. Kohno et al (2012) suggested evaluating resilience by taking into account the areas where the organization's facilities are located, the infrastructure the organization needs, the organization facilities and the supply chains.…”
Section: Measuring Organizational Resilience Based On Indicatorsmentioning
confidence: 99%
“…It is a capacity of the organization to observe and understand what is going on in all its internal and external environment, and how variations can interfere positively or negatively in the organization. (MCMANUS, SEVILLE, VARGO et al, 2008;SANCHIS and POLER, 2013). In this sense, organizational resilience is understood as the ability of the company to minimize risks and their effects, whether threatening situations are previously known or not, transforming and responding quickly as threats and opportunities are perceived, which McManus, Seville, Vargo et al (2008) called 'resilience management'.…”
Section: The Evolution Of the Organizational Resilience Conceptmentioning
confidence: 99%